Genetic Diversity of Cryptosporidium in Children in an Urban Informal Settlement of Nairobi, Kenya - Mbae, Cecilia; Mulinge, Erastus; Waruru, Anthony; Ngugi, Benjamin; Wainaina, James; Kariuki, Samuel (Public Library of Science, 2015)
Globally Cryptosporidium and Giardia species are the most common non-bacterial causes of diarrhoea in children and HIV infected individuals, yet data on their role in paediatric diarrhoea in Kenya remains scant. This study investigated the occurrence of Cryptosporidium species, genotypes and subtypes in children, both hospitalized and living in an informal settlement in Nairobi.